Os conceitos normatizados pela legislaçao e a interpretaçao da estrutura agrária e fundiária no Brasil - Talaska, Alcione (2016)
Considering agrarian legislation of the last 50 years, this article expressed the objetive to identify and describe the concepts that are used for the characterization and understanding of the conformation of the brazilian agrarian space. We noted, in this context, a process of change in the laws, which suppressed the concepts of latifundio (landlordism) and minifundio (small parcels property), which created concepts of small property, of average property, of productive property and of family agriculture, but which not considered other important definitions: large farms and paternal agriculture. This substitution of interpretative concepts limits the understanding of the brazilian agrarian dynamics, especially if we consider the analysis of contradictory process of development capitalism in the field, in Brazil.